Making it like a man : Canadian masculinities in practice - Ramsay, Christine, 1958- (Cultural studies series (Waterloo, Ont.), 2011)
Making It Like a Man: Canadian Masculinities in Practice is a collection of essays on the practice of masculinities in Canadian arts and cultures, where to make it like a man is to participate in the cultural, sociological, and historical fluidity of ways of being a man in Canada, from the country's origins in nineteenth-century Victorian values to its immersion in the contemporary post-modern landscape. The book focuses on the ways Canadian masculinities have been performed and represented through five broad themes: colonialism, nationalism, and transnationalism; emotion and affect; ethnic and minority identities; capitalist and domestic politics; and the question of men's relationships with themselves and others. Chapters include studies of well-known and more obscure figures in the Canadian arts and culture scenes, such as visual artist Attila Richard Lukacs; writers Douglas Coupland, Barbara Gowdy, Simon Chaput, Thomas King, and James De Mille; filmmakers Clement Virgo, Norma Bailey, John N. Smith, and Frank Cole; as well as familiar and not-so-familiar tokens of Canadian masculinity such as the hockey hero, the gangsta rapper, the immigrant farmer, and the drag king. Making It Like a Man is the first book of its kind to explore and critique historical and contemporary masculinities in Canada with a special focus on artistic and cultural production and representation. It is concerned with mapping some of the uniquely Canadian places and spaces in the international field of masculinity studies, and will be of interest to academic and culturally informed audiences. About Christine Ramsay Christine Ramsay is an associate professor in media studies at the University of Regina, Saskatchewan.